PENGELOLAAN PEMBELAJARAN IPA OLEH GURU BERSERTIFIKAT PENDIDIK ( STUDI SITUS DI SMP NEGERI 1 DEMAK ) - WIDAYAT , AGUS EKO WAHYU (2011)
One of the main factors which determines the education quality is a teacher. By the teacher, the students quality will be accomplished, from academic, skill, the mature of emotionality, moral and spiritual. In order to increase the education quality it needs a professional teacher that has good qualification, competition, and dedication to manage the learning process. The purpose of this research is to describe the characteristics management of science instructional by a teacher's certification in State Junior High School 1 Demak Regency, consisting of: 1) The characteristics of Sciences subject, 2) The characteristic of science learning interaction, and 3) The characteristics of science teacher's certification activities outside the class. This research used qualitative research with ethnography strategy. The location was in State Junior High School 1 Demak Regency. The instrument of this research is researcher herself. The data collect on of this research consist of : 1) the material discussed in the science instructional; 2 ) the science instructional interaction done by a teacher in the class; and 3) the teacher's certification activities outside the class. The primary source of the research is science teacher's certificate, students, and the vice principal of academic affair. Collecting data is from: in depth interview, participant observation and documentation study. The technique of data analysis used analysis data in site. Validity of the data that used in this research were: triangulation, dependability, and confirm ability. This research results that science subject in State Junior High School 1 Demak has some characteristics: science subject consists of physics and biology which are taught every semester by physics teacher and biology teacher, with time allocation 6 (six) lesson hours every week by increasing material of National Science Olympic (NSO), teacher does subject analysis and improves the subject from every learning sources. The interaction of science instructional has characteristics: the science instructional done by the teacher is based on the lesson plan, the science instructional focused to the students, prior to skill process, the teacher as facilitator, the instructional method are discussed, and practice, the science instructional use e-learning, teacher carries on evaluation and the teacher follow up evaluation results. The characteristic science teacher's certification activities outside the class are: The teacher use their spare time to do activities to improve their capability in ICT (Information and Communication Technology), teacher hold Association of Teacher Learning Subject (ATLS) either in school, regency and also province, teacher does activities outside the school related to their profession.